1997
DOI: 10.1086/514873
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reversals in Predictive Testing for Huntington Disease

Abstract: The first predictive testing for Huntington disease (HD) was based on analysis of linked polymorphic DNA markers to estimate the likelihood of inheriting the mutation for HD. Limits to accuracy included recombination between the DNA markers and the mutation, pedigree structure, and whether DNA samples were available from family members. With direct tests for the HD mutation, we have assessed the accuracy of results obtained by linkage approaches when requested to do so by the test individuals. For six such ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In the older literature about half of the articles that mentioned a solution suggested involving patients in the process of recontacting. 1,7,10,12,18,21,23,25 Patients could contribute by, for example, contacting the department regularly to inquire about new genetic information, keep the genetics department up to date regarding address and personal information, and checking for new genetic developments on websites. Fitzpatrick et al 12 suggested including informing the media, support groups, and other health professionals in the recontacting process.…”
Section: Recontact In Clinical Genetics: Practical Barriers and Solutmentioning
confidence: 99%
“…In the older literature about half of the articles that mentioned a solution suggested involving patients in the process of recontacting. 1,7,10,12,18,21,23,25 Patients could contribute by, for example, contacting the department regularly to inquire about new genetic information, keep the genetics department up to date regarding address and personal information, and checking for new genetic developments on websites. Fitzpatrick et al 12 suggested including informing the media, support groups, and other health professionals in the recontacting process.…”
Section: Recontact In Clinical Genetics: Practical Barriers and Solutmentioning
confidence: 99%
“…The low percentage of those being retested may relate to the percentage error of the linkage test, which affords a small window of hope for error in those whose test results show that they are at increased risk. Conversely, people who have had a linkage result showing decreased risk may not wish to jeopardize their status by discovering a risk reversal with a more accurate test (33).…”
Section: Predictive Testingmentioning
confidence: 99%
“…A total of 107 centers from 20 countries provided data on 5,781 tested individuals. Most catastrophic events occur within 1 year after the test result: 5 individuals committed suicide and 16 attempted suicide [Almqvist and Bloch, 1996]. However, to designate predictive testing for HD as a ''success story'' [Bundey, 1997] is an underestimation of the complicated psychological process that the majority of tested individuals, their partners, and their relatives have to go through, as was emphasized by workers from the first hour [Evers-Kiebooms, et al, 1997;Mlynik-Szmid, 1997;Tibben et al, 1997a].…”
Section: Predictive Testing For Huntington Disease Versus Predictive mentioning
confidence: 99%